2019
DOI: 10.3390/ma12060991
|View full text |Cite
|
Sign up to set email alerts
|

Laser Polishing of Additive Manufactured 316L Stainless Steel Synthesized by Selective Laser Melting

Abstract: One of the established limitations of metal additive manufacturing (AM) methods, such as selective laser melting (SLM), is the resulting rough surface finish. Laser polishing is one method that can be used to achieve an improved surface finish on AM printed parts. This study is focused on the laser surface polishing of AM parts using CO2 laser beam irradiation. Despite the fact that several researchers have investigated the traditional abrasive polishing method, there is still a lack of information reporting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 33 publications
1
44
0
Order By: Relevance
“…SLM of austenitic stainless steels can be performed under a wide variety of process parameters including laser power (68–400 W), scan speed (0.3–2.5 m/s), layer thickness (20–50 μm), and hatch distance; the distance between the centre of two adjacent melt pools (40–140 μm) [4,5,6,7,8,9,10,11,12,13,14,15]. Therefore, depending on the process parameters, the alloy may experience a wide variety of temperature gradients, solidification conditions, thermal stresses, and be susceptible to defects such as cracks, pores, and residual stresses.…”
Section: Introductionmentioning
confidence: 99%
“…SLM of austenitic stainless steels can be performed under a wide variety of process parameters including laser power (68–400 W), scan speed (0.3–2.5 m/s), layer thickness (20–50 μm), and hatch distance; the distance between the centre of two adjacent melt pools (40–140 μm) [4,5,6,7,8,9,10,11,12,13,14,15]. Therefore, depending on the process parameters, the alloy may experience a wide variety of temperature gradients, solidification conditions, thermal stresses, and be susceptible to defects such as cracks, pores, and residual stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Other groups have had more success with thermally based treatments. Obeidi et al [ 58 ] successfully reduced the average surface roughness of stainless steel cylinders via laser polishing. This method has the benefit of avoiding the residual debris discussed above, but again may be difficult to apply to more complex shapes.…”
Section: Discussionmentioning
confidence: 99%
“…It is the lower hatching space that can be chosen to reduce more surface roughness. Obeidi et al [ 32 ] also found that increasing the overlapping area could improve the surface quality of AM 316L.…”
Section: Methodsmentioning
confidence: 99%